2022
DOI: 10.1038/s41598-022-21851-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum kisspeptin and proopiomelanocortin in cystic fibrosis: a single study

Abstract: The determination of hormonal biomarkers is of increasing interest in many diseases, including cystic fibrosis (CF). Hormones that have not been estimated and described so far in CF include kisspeptin (KISS) and proopiomelanocortin (POMC), which are involved in the regulation of many processes, including appetite and fertility. Therefore, the aim of our study was to estimate the level of KISS and POMC in sera from CF patients and to determine the correlation between these hormones and clinical parameters. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…To date, there are only a few reports on the determination of POMC in serum using the immunoenzymatic method. Our recent study in cystic fibrosis patients showed reduced POMC levels compared to controls [ 31 ]. On the other hand, patients with anorexia nervosa have shown significantly higher levels of POMC than controls [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are only a few reports on the determination of POMC in serum using the immunoenzymatic method. Our recent study in cystic fibrosis patients showed reduced POMC levels compared to controls [ 31 ]. On the other hand, patients with anorexia nervosa have shown significantly higher levels of POMC than controls [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it appears that the low body mass in CF patients may be associated with disturbances in the levels of hormones that regulate appetite [13,14]. Currently, reports on levels of appetite-regulating hormones in CF are inconclusive and suggest that, in addition to the disease itself, many factors, including types of CFTR mutations, lifestyle, and nutrition, may influence hormone levels [13,14,[32][33][34][35]. Moreover, hormonal disorders of CF are more common in the elderly and are expected to become more frequent as medical care improves and the population ages [36,37].…”
Section: Discussionmentioning
confidence: 99%